PROBLEMS OF FUNCTIONING OF THE INTERNATIONAL TOURIST INDUSTRY IN THE CONDITIONS OF A GLOBAL PANDEMIC - RYBCHUK, ANATOLIY; ZHURBA, IHOR; ZABLOTSKA, RITA (Herald of Khmelnytskyi National University. Economic sciences, 2022)
Modern tourism is called a phenomenon of the twentieth century and an important area of the global economy, because it has acquired the features of a separate sector of the world economy and is characterized by significant volumes of international trade in its own services. In recent decades, the tourism industry has been characterized by high and stable rates of development, which have contributed not only to the expansion of socio-economic and political relations between countries, but also to replenish budgets at the macro level. Tourism is influenced by many factors of economic, political, social, natural and technical nature, including: international terrorism, ensuring the safety of tourists, man-made disasters; uneven distribution of tourist flows; political instability in some parts of the world; prolonged global recession.The article examines the features and problems of the international tourism industry in a global pandemic. Scenarios of possible reduction of the number of tourists and income from travel are revealed. The peculiarities of the development of modern tourism, which is the transformation of tourism organizations into international joint ventures, corporations and associations are noted. New opportunities and challenges of serious testing for the whole tourist market are presented, which are conditioned by the acceleration of digitalization of tourist services, more active introduction of modern technologies, updating of the individual approach to the client. It was confirmed that the states are taking measures to protect, attract and promote investment projects in tourism in order to speed up the recovery of national economies. It is proved that the leading function in the international transportation of tourists is air and sea transport. Expectations of growth in the number of international tourist trips in the near future have been revealed.
Keywords: international tourism; tourist market; tourist product; tourism industry; tourist services; tourist investment projects